Free radical scavenging, in vivo antioxidant and hepatoprotective activity of folk medicine Trichodesma sedgwickianum - Shweta S. Saboo; Ganesh Tapadiya; I. A. Farooqui; S. S. Khadabadi (Bangladesh Pharmacological Society, 2013)
Trichodesma sedgwickianum has been used in folk medicine possessing anti-inflammatory and hepatoprotective activity. This led us to investigate for its antioxidant and hepatoprotective potential. Different polarities extracts were subjected to polyphenolic estimation and in vitro antioxidant activity. The potential extract was tested for in vivo antioxidant and hepatoprotective activity, assessed by carbon tetrachloride-induced oxidative stress in rats.  Phytochemical identification of major constituents has been carried out by HPLC, GC-MS, 1HNMR and 13C NMR. Amongst the extracts, successive ethanol extract showed higher concentration of polyphenols (25.4 ± 0.1% w/w) and in vitro antioxidant property. The in vivo antioxidant efficiency was confirmed by comparing the enzymatic level, superoxide dismutase, catalase, reduced glutathione and MDA in test group with the standard and control. Hepatoprotective effect was observed by changes in the serum enzyme level which were further supported by histological examination. Phytochemically ethanol extract contains gallic acid and catechin along with other constituents. Thus present study provides a scientific rationale for their traditional use.